Introduction to tunnel construction - Chapman, David N.; Metje, Nicole; Stärk, Alfred (CRC Press, 2017)
"Tunnelling provides a robust solution to a variety of engineering challenges. It is a complex process, which requires a firm understanding of the ground conditions as well as the importance of ground-structure interaction. This book covers the full range of areas related to tunnel construction required to embark upon a career in tunnelling. It also includes a number of case studies related to real tunnel projects, to demonstrate how the theory applies in practice. New features of this second edition include: the introduction of a case study related to Crossrail's project in London, focussing on the Whitechapel and Liverpool Street station tunnels and including considerations of building tunnels in a congested urban area; and further information on recent developments in tunnel boring machines, including further examples of all the different types of machine as well as multi-mode machines. The coverage includes:Both hard-rock and soft-ground conditionsSite investigation, parameter selection, and design considerationsMethods of improving the stability of the ground and lining techniquesDescriptions of the various main tunnelling techniquesHealth and safety considerationsMonitoring of tunnels during constructionDescription of the latest tunnel boring machinesCase studies with real examples, including Crossrail's project in LondonClear, concise, and heavily illustrated, this is a vital text for final-year undergraduate and MSc students and an invaluable starting point for young professionals and novices in tunnelling."--Provided by publisher
Keywords: Tunnels -- Design and construction.; Tunneling.; elektronické knihy; electronic books